Host responses induced by different animal models of periodontal disease: a literature review - Molon, Rafael Scaf de; Avila, Erica Dorigatti de; Cirelli, Joni Augusto [UNESP] (Wiley, 2012)
Periodontitis is an infectious disease characterized by chronic inflammation of the periodontium, and it is mediated and modulated by the host immune system. In the presence of microorganisms or other antigens, immune cells (macrophages/monocytes, dendritic cells, lymphocytes, neutrophils), endothelial cells and fibroblasts secrete cytokines and trigger immune and inflammatory reactions. However, when synthesized at high levels, cytokines modify the pattern of cellular response, participating substantially in the development of chronic inflammatory pathologies, such as periodontal disease. Understanding the origin and progression of bone resorption is one of the primary goals of the field of periodontics, aiming to arrest the disease progression and to optimize future treatments. For this purpose, the development of experimental models is an important and necessary step before entering into clinical trials with new therapies. The purpose of this study is to characterize/evaluate the tissue changes induced by various models of experimental periodontitis through a literature review.
Keywords: cytokines; experimental models; periodontal disease